Multi-layered polyimide film and its manufacturing method

A multilayer polyimide film with specific compositions and layer configurations addresses high dielectric loss and instability issues, providing stable, high-speed communication and insulation in flexible circuit boards.

JP2024545860AActive Publication Date: 2024-12-13PI ADVANCED MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024531184
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-24
Filing Date
2022-11-23
Publication Date
2024-12-13
Estimated Expiration
2042-11-23

AI Technical Summary

Technical Problem

Existing polyimide films face challenges with high dielectric constants and dielectric loss factors, leading to insufficient insulation and signal interference in high-frequency communications, along with unstable dimensional changes during lamination due to high temperatures, affecting the quality and efficiency of flexible circuit boards.

Method used

A multilayer polyimide film structure is developed with specific compositions and layer configurations, including a core layer and skin layers, using varying ratios of dianhydride acid and diamine components, to achieve low dielectric loss and high adhesive strength, suitable for high-frequency communications.

Benefits of technology

The multilayer polyimide film maintains excellent adhesive strength and low dielectric properties, ensuring stable and efficient high-speed transmission and communication, while minimizing signal interference and maintaining dimensional stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024545860000001
    Figure 2024545860000001
  • Figure 2024545860000002
    Figure 2024545860000002
  • Figure 2024545860000003
    Figure 2024545860000003
Patent Text Reader

Abstract

The present invention provides a multilayer polyimide film that includes at least one skin layer formed on at least one outer surface of a core layer, has a dielectric loss factor of 0.003 or less, and an adhesive strength of 1,000 gf / cm or more, and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer polyimide film having low dielectric constant and excellent adhesive properties, and a method for producing the same. [Background technology]

[0002] Polyimide (PI) is a polymeric material based on imide rings, which have excellent chemical stability along with a rigid aromatic main chain, and has the highest levels of heat resistance, chemical resistance, electrical insulation, chemical resistance, and weather resistance among organic materials. In addition, due to its excellent electrical properties, such as insulating properties and low dielectric constant, it is attracting attention as a highly functional polymer material in fields including microelectronics and optics. In the field of microelectronics, for example, due to the need to make electronic products lighter and smaller, highly integrated and flexible thin circuit boards have been actively developed, and such thin circuit boards tend to be made of a structure in which a circuit containing metal foil is formed on a polyimide film that has excellent heat resistance, low temperature resistance, and insulating properties, but is also easily bent. Such thin circuit boards are also called flexible metal foil laminates in a broad sense, and when a thin copper plate is used as the metal foil, they are also called flexible copper clad laminates (FCCL) in a narrow sense. Polyimides are also used as protective films, insulating films, etc. for thin circuit boards.

[0003] Examples of methods for producing flexible metal foil laminates include (i) a casting method in which polyamic acid, a precursor of polyimide, is cast or coated onto a metal foil and then imidized; (ii) a metallizing method in which a metal layer is directly formed on a polyimide film by sputtering or plating; and (iii) a lamination method in which a polyimide film and a metal foil are bonded together by heat and pressure using a thermoplastic polyimide. Among these, the lamination method has the advantage that the applicable range of metal foil thickness is wider than that of the casting method, and the equipment cost is cheaper than that of the metallizing method. As an equipment for laminating, a roll laminating equipment that continuously laminates while feeding a roll-shaped material, or a double belt press equipment, etc. are used. Among the above, from the viewpoint of productivity, the hot roll lamination method using a hot roll laminating equipment is more preferably used. However, in the case of lamination, as mentioned above, a thermoplastic resin is used to bond the polyimide film and the metal foil, and in order to express the thermal fusion properties of this thermoplastic resin, it is necessary to apply heat of 300°C or more to the polyimide film, and in some cases, heat of 400°C or more, which is close to or higher than the glass transition temperature (Tg) of the polyimide film.

[0004] It is generally known that the storage modulus of a viscoelastic material such as a polyimide film is significantly reduced in a temperature range exceeding the glass transition temperature compared to the value at room temperature. That is, when lamination is performed at a high temperature, the storage modulus of the polyimide film is significantly decreased at high temperatures, and the polyimide film is likely to be loose at a low storage modulus, and therefore not have a flat shape after lamination is completed. In other words, the dimensional change of the polyimide film is relatively unstable during lamination. Another point to note is that when the glass transition temperature of the polyimide film is significantly lower than the temperature at which lamination is performed, the viscosity of the polyimide film is relatively high at the lamination temperature, which results in a relatively large change in dimensions, and this may result in a deterioration in the appearance quality of the polyimide film after lamination. Therefore, there is currently a high demand for technology that can solve the above problems and greatly improve processability.

[0005] Meanwhile, as electronic devices have recently been equipped with various functions, there is a demand for high calculation speeds and communication speeds in the electronic devices. To meet this demand, thin circuit boards that have low dielectric loss rate even at high frequencies of 10 GHz or more and enable high-speed communication transmission have been developed. To realize high-frequency, high-speed communications, insulators that have high impedance and can maintain electrical insulation even at high frequencies are required. Since impedance is inversely proportional to the frequency and dielectric constant (Dk) formed in an insulator, the dielectric constant must be as low as possible to maintain insulation even at high frequencies. However, in the case of ordinary polyimides, the dielectric constant is about 3.4 to 3.6, which is not excellent enough to maintain sufficient insulation in high-frequency communications. For example, in a thin circuit board in which high-frequency communications of 10 GHz or more are performed, there is a possibility that the insulation may be partially or entirely lost.

[0006] In addition, it is known that the lower the dielectric constant of an insulator, the more likely it is that unwanted stray capacitance and noise will be reduced in thin circuit boards, and this can largely eliminate the causes of communication delays. Therefore, making the dielectric constant of polyimide as low as possible is currently recognized as the most important factor in the performance of thin circuit boards. Another thing to note is that in the case of high-frequency communications of 10 GHz or more, dielectric dissipation inevitably occurs due to polyimide. The dielectric dissipation factor (Df) refers to the degree of electrical energy wasted in a thin circuit board and is closely related to the signal transmission delay that determines the communication speed. Therefore, minimizing the dielectric loss factor of polyimide is recognized as an important factor in the performance of thin circuit boards. Therefore, there is a need to develop a polyimide film that has a relatively low dielectric loss factor and high adhesive strength, enabling stable circuitry to be realized, and an effective method for manufacturing the same. The matters described in the above background art are intended to aid in understanding the background of the invention, and may include matters that are not prior art already known to those having ordinary skill in the art to which this technology pertains. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Republic of Korea Patent Publication No. 10-2012-0133807 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of one aspect of the present invention is to provide a multilayer polyimide film having excellent adhesion and a relatively low dielectric loss factor, and an effective method for producing the same. Specifically, the object is to provide a polyimide film having excellent adhesion and a low dielectric loss value even at high frequencies, which is achieved by determining the type of dianhydride, the type of diamine, and the compounding ratio thereof and by constructing the film from multiple layers of polyimide resins having mutually different compositions. Another object of the present invention is to provide a flexible copper foil laminate that includes a multi-layer polyimide film having excellent adhesive strength and a relatively low dielectric loss factor, and is effective for high-speed transmission and high-speed communication at high frequencies. Therefore, a substantial object of the present invention is to provide specific examples thereof. However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0009] In order to achieve the above object, one aspect of the present invention is a heat-resistant sheet comprising at least one skin layer formed on at least one outer surface of a core layer, The dielectric loss factor is 0.003 or less, and the adhesive strength is 1,000gf / cm or more. A multi-layer polyimide film is provided. Another aspect of the present invention is a multilayer polyimide film comprising the multilayer polyimide film and an electrically conductive metal foil, A flexible metal foil laminate is provided. Yet another aspect of the present invention includes the flexible metal foil laminate, Provide electronic components. Effect of the Invention

[0010] The present invention provides a polyimide film having excellent low dielectric properties and adhesive properties by adjusting the composition ratio and reaction ratio of dianhydride and diamine components. Another object of the present invention is to provide a flexible copper foil laminate that includes a multi-layer polyimide film having excellent adhesive strength and a relatively low dielectric loss factor, and is effective for high-speed transmission and high-speed communication at high frequencies. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to explain his / her invention in the best possible way. Therefore, it should be understood that the configuration of the embodiment described in this specification is merely one of the most preferred embodiments of the present invention and does not fully represent the technical ideas of the present invention, and that there may be various equivalents and modifications that can replace them at the time of this application. In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0012] As used herein, "dianhydride acid" is intended to include precursors or derivatives thereof which may not technically be dianhydrides but which nevertheless must react with a diamine to form a polyamic acid which is then converted back to a polyimide. As used herein, "diamine" is intended to include precursors or derivatives thereof, which may not technically be diamines, but which nevertheless must react with a dianhydride to form a polyamic acid, which is then converted back to a polyimide. Whenever an amount, concentration, or other value or parameter is given herein as a range, a preferred range or a list of an upper preferred value and a lower preferred value, it should be understood to specifically disclose all ranges formed by any pair of any upper range limit or preferred value, and any lower range limit or preferred value, regardless of whether a range is otherwise disclosed. Where a range of numerical values ​​is recited herein, unless otherwise stated, the range is intended to include the endpoints thereof, and all integers and fractions within the range. It is not intended that the scope of the invention be limited to the specific values ​​recited when defining a range. According to one embodiment of the present invention, there is provided a multilayer polyimide film comprising at least one skin layer formed on at least one outer surface of a core layer, the skin layer having a dielectric loss factor of 0.003 or less, The adhesive strength may be 1,000 gf / cm or more.

[0013] In one embodiment, the insulating film has a three-layer structure including the skin layers formed on one outer surface of the core layer and on the opposite outer surface of the core layer. The dianhydride and diamine components and their composition ratios in the skin layers formed on one outer surface and the opposite outer surface of the core layer, respectively, may be the same or different. In addition, the thicknesses of the skin layers formed on one outer surface of the core layer and the opposite surface of the outer surface may be the same or different.

[0014] In one embodiment, the three-layer polyimide film may have a total thickness of 10 μm to 100 μm, a thickness of the core layer may be 70% to 95% of the total thickness of the multilayer polyimide film, and a total thickness of the skin layers formed on one outer side of the core layer and on the opposite side of the outer side may be 5% to 30% of the total thickness of the multilayer polyimide film. For example, the thickness of the core layer may be 35 μm or more and 45 μm or less, and the thickness of the one skin layer may be 2.5 μm or more and 7.5 μm or less. If the thickness of the core layer and / or the skin layer is greater than or less than the above range, the dielectric loss factor of the multilayer polyimide film may increase, resulting in a decrease in low dielectric properties or a decrease in adhesive strength.

[0015] In one embodiment, the core layer is obtained by imidizing a polyamic acid solution containing a dianhydride component including biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA) and a diamine component including paraphenylenediamine (PPD) and m-tolidine, and the skin layer is obtained by imidizing a polyamic acid solution containing a dianhydride component including biphenyltetracarboxylic dianhydride and pyromellitic dianhydride and a diamine component including paraphenylenediamine, m-tolidine, and oxydianiline (ODA). In one embodiment, in the core layer, the content of the biphenyltetracarboxylic dianhydride is 50 mol% or more and 70 mol% or less, the content of the pyromellitic dianhydride is 30 mol% or more and 50 mol% or less, based on a total content of the dianhydride acid components of 100 mol%, and the content of the paraphenylenediamine is 60 mol% or more and 80 mol% or less, and the content of the m-tolidine is 20 mol% or more and 40 mol% or less, based on a total content of the diamine components of 100 mol%.

[0016] In one embodiment, the core layer may comprise a block copolymer comprising two or more blocks. The block copolymer of the core layer includes a first block containing 50 mol % or more and 60 mol % or less of the biphenyltetracarboxylic dianhydride based on 100 mol % of the total content of dianhydride acid components in the polyimide film, and a second block containing 30 mol % or more and 40 mol % or less of the m-tolidine based on 100 mol % of the total content of diamine components in the polyimide film. The first block may be obtained by imidizing biphenyltetracarboxylic dianhydride with paraphenylenediamine, and the second block may be obtained by imidizing m-tolidine with pyromellitic dianhydride. Alternatively, all of the biphenyltetracarboxylic dianhydride in the first block may be imidized with paraphenylenediamine, and all of the m-tolidine in the second block may be imidized with pyromellitic dianhydride.

[0017] In one embodiment, the skin layer contains 100 mol % of the dianhydride acid component. As a standard, the content of the biphenyltetracarboxylic dianhydride may be 30 mol% or more and 50 mol% or less, the content of the pyromellitic dianhydride may be 50 mol% or more and 70 mol% or less, and the content of the paraphenylenediamine may be 5 mol% or more and 25 mol% or less, the content of m-tolidine may be 60 mol% or more and 80 mol% or less, and the content of the oxydianiline may be 5 mol% or more and 25 mol% or less, based on a total content of the diamine components of 100 mol%. As the content of the paraphenylenediamine of the present invention is increased as a rigid monomer, the polyimide synthesized has a more linear structure, which contributes to improving the mechanical properties of the polyimide. Furthermore, m-tolidine, in particular, has a methyl group that exhibits hydrophobicity, and contributes to the low moisture absorption characteristic related to the dimensional stability of the polyimide film against moisture.

[0018] The polyimide chain derived from the biphenyltetracarboxylic dianhydride of the present invention has a structure called a charge transfer complex (CTC), i.e., a regular linear structure in which an electron donor and an electron acceptor are placed close to each other, and intermolecular interactions are strengthened. Such a structure has an effect of preventing hydrogen bonding with moisture, which has an effect of lowering the moisture absorption rate, thereby maximizing the effect of reducing the moisture absorption of the polyimide film, which affects the dimensional stability against moisture. In addition, pyromellitic dianhydride is a dianhydride acid component having a relatively rigid structure, and is preferable in that it can impart suitable elasticity to the polyimide film. In order for the polyimide film to have excellent dimensional stability, the content ratio of the dianhydride acid is important. For example, as the content ratio of biphenyltetracarboxylic dianhydride decreases, it becomes difficult to expect a low moisture absorption rate due to the CTC structure, and the dimensional stability against moisture also decreases.

[0019] In addition, biphenyltetracarboxylic dianhydride contains two benzene rings corresponding to the aromatic moiety, whereas pyromelitic dianhydride contains one benzene ring corresponding to the aromatic moiety. An increase in the content of pyromellitic dianhydride in the dianhydride acid component can be understood as an increase in the imide groups in the molecule based on the same molecular weight, which can be understood as a relative increase in the ratio of imide groups derived from the pyromellitic dianhydride in the polyimide polymer chain compared to the imide groups derived from biphenyltetracarboxylic dianhydride. In other words, an increase in the content of pyromellitic dianhydride is seen as a relative increase in imide groups with respect to the entire polyimide film, and this makes it difficult to expect high dimensional stability against moisture due to a low moisture absorption rate. Conversely, if the content ratio of the pyromellitic dianhydride is decreased, the components having a relatively rigid structure are decreased, and the elasticity of the polyimide film may be decreased below a desired level.

[0020] For these reasons, when the content of the biphenyltetracarboxylic dianhydride exceeds the above range or the content of the pyromellitic dianhydride is below the above range, the dimensional stability of the polyimide film may decrease. Conversely, if the content of the biphenyltetracarboxylic dianhydride is below the above range or the content of the pyromellitic dianhydride is above the above range, the dimensional stability of the polyimide film may also be adversely affected.

[0021] In the present invention, the polyamic acid can be produced, for example, by (1) A method in which the entire amount of the diamine component is placed in a solvent, and then the dianhydride component is added in an amount substantially equimolar to the diamine component to polymerize it; (2) A method in which the entire amount of the dianhydride component is placed in a solvent, and then a diamine component is added in an amount substantially equimolar to the dianhydride component to polymerize it; (3) A method in which a part of the diamine component is placed in a solvent, a part of the dianhydride component is mixed with the reaction components in a ratio of about 95 to 105 mol %, the remaining diamine component is added, and the remaining dianhydride component is added successively thereto, so that the diamine component and the dianhydride component are polymerized in substantially equimolar amounts; (4) A method in which a dianhydride component is placed in a solvent, a part of the components in the diamine compound is mixed in a ratio of 95 to 105 mol % relative to the reactive components, and then another dianhydride component is added, followed by the remaining diamine component, so that the diamine component and the dianhydride component are substantially equimolar, thereby polymerizing the mixture; (5) A method of forming a first composition by reacting some diamine components and some dianhydride acid components in a solvent so that one of them is in excess, and forming a second composition by reacting some diamine components and some dianhydride acid components in another solvent so that one of them is in excess, and then mixing the first and second compositions to complete polymerization, in which if the diamine component is in excess when the first composition is formed, the dianhydride acid component is in excess in the second composition, and if the dianhydride acid component is in excess in the first composition, the diamine component is in excess in the second composition, and the first and second compositions are mixed to polymerize so that the total diamine components and dianhydride acid components used in these reactions are substantially equimolar.

[0022] In the present invention, the polymerization method of the polyamic acid as described above can be defined as a random polymerization method, and the polyimide film prepared from the polyamic acid of the present invention prepared by the above process can be preferably applied in terms of maximizing the effects of the present invention, which are to improve dimensional stability and chemical resistance. However, in the above polymerization method, the length of the repeating unit in the polymer chain is relatively short as described above, so that there may be a limit to the excellent properties of the polyimide chain derived from the dianhydride acid component. Therefore, the polymerization method of polyamic acid that can be particularly preferably used in the present invention is the block polymerization method. On the other hand, the solvent for synthesizing the polyamic acid is not particularly limited, and any solvent that dissolves the polyamic acid can be used, but an amide-based solvent is preferable.

[0023] Specifically, the organic solvent may be an organic polar solvent, more specifically, an aprotic polar solvent, for example, one or more selected from the group consisting of N,N-dimethylformamide (DMF), N,N-dimethylacetamide, N-methyl-pyrrolidone (NMP), gamma-butyrolactone (GBL), and diglyme, but is not limited thereto, and may be used alone or in combination of two or more kinds as needed. In one example, the organic solvent is preferably N,N-dimethylformamide or N,N-dimethylacetamide.

[0024] In addition, in the process for producing the polyamic acid, a filler may be added for the purpose of improving various properties of the film such as sliding properties, thermal conductivity, corona resistance, loop hardness, etc. The filler to be added is not particularly limited, but preferred examples include silica, titanium oxide, alumina, silicon nitride, boron nitride, calcium hydrogen phosphate, calcium phosphate, mica, etc. The particle size of the filler is not particularly limited and may be determined depending on the film properties to be modified and the type of filler to be added. In general, the average particle size is 0.05 to 100 μm, and preferably The thickness is preferably 0.1 to 75 μm, more preferably 0.1 to 50 μm, and particularly preferably 0.1 to 25 μm. If the particle size is below this range, the modifying effect is unlikely to be achieved, whereas if it exceeds this range, the surface properties may be significantly damaged or the mechanical properties may be significantly reduced.

[0025] The amount of the filler to be added is not particularly limited, and may be determined depending on the film properties to be modified, the particle size of the filler, etc. In general, the amount of the filler to be added is 0.01 to 100 parts by weight, preferably 0.01 to 90 parts by weight, and more preferably 0.02 to 80 parts by weight, relative to 100 parts by weight of polyimide. If the amount of the filler added is less than this range, the modifying effect of the filler is unlikely to be exhibited, and if the amount exceeds this range, the mechanical properties of the film may be significantly damaged. The method of adding the filler is not particularly limited, and any known method may be used. In the production method of the present invention, the polyimide film is produced by a thermal imidization method and a chemical imidization method.

[0026] Alternatively, the imidation layer may be produced by a hybrid imidation method in which a thermal imidization method and a chemical imidization method are performed in parallel. The thermal imidization method is a method in which a chemical catalyst is excluded and the imidization reaction is induced by a heat source such as hot air or an infrared dryer. The thermal imidization method can imidize the amic acid groups present in the gel film by heat-treating the gel film at a variable temperature in the range of 100 to 600°C, specifically, 200 to 500°C, more specifically, 300 to 500°C.

[0027] However, even during the process of forming the gel film, a portion of the amic acid (approximately 0.1 mol % to 10 mol %) is imidized, and therefore the polyamic acid composition can be dried at a variable temperature in the range of 50°C to 200°C, which also falls within the category of the thermal imidization method. In the case of the chemical imidization method, a polyimide film can be produced using a dehydrating agent and an imidization agent by methods known in the art. As an example of the composite imidization method, a polyimide film can be produced by adding a dehydrating agent and an imidization agent to a polyamic acid solution, heating the solution at 80 to 200°C, preferably 100 to 180°C, partially curing and drying the solution, and then heating the solution at 200 to 400°C for 5 to 400 seconds.

[0028] Meanwhile, the multi-layer polyimide film of the present invention described above can be manufactured by using at least one of coextrusion and coating. In the co-extrusion method, a polyamic acid solution or a polyimide resin produced by imidizing the polyamic acid solution is filled in a storage tank, and then the solution is extruded in multiple layers onto a casting belt using a co-extrusion die, and then cured to produce a multi-layered polyimide film. This method has high productivity and ensures high interfacial adhesion reliability by mixing different types of polyimide resins at the interfaces. For example, a method for producing a multilayer polyimide film of the present invention includes a first filling step of filling a first storage tank with a first solution, which is a first polyamic acid solution or a first polyimide resin produced by imidizing the first polyamic acid solution; a second filling step of filling a second storage tank with a second solution, which is a second polyamic acid solution or a second polyimide resin produced by imidizing the second polyamic acid solution; a co-extrusion step of co-extruding the first and second solutions through a co-extrusion die having a first flow path connected to the first storage tank, a second flow path connected to the second storage tank, and a third flow path connected to the second storage tank, respectively; and a curing step of curing the first and second solutions extruded.

[0029] The first polyamic acid solution is for forming a core layer, and is a biphenyltetracarboxylic acid solution. It is preferably produced by polymerizing a dianhydride component including boxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA) with a diamine component including paraphenylenediamine (PPD) and m-tolidine. The second polyamic acid solution is for forming a skin layer and is preferably produced by polymerizing a dianhydride acid component including biphenyltetracarboxylic dianhydride and pyromellitic dianhydride, and a diamine component including paraphenylenediamine, m-tolidine, and oxydianiline (ODA). Meanwhile, when the first polyamic acid solution is used as the first solution and the second polyamic acid solution is used as the second solution, it is preferable to further include an imidization step of imidizing the first and second solutions co-extruded before the curing step. The present invention provides a flexible metal foil laminate comprising the above-mentioned multilayer polyimide film and an electrically conductive metal foil.

[0030] The metal foil used is not particularly limited, but when the flexible metal foil laminate of the present invention is used for electronic or electrical equipment, the metal foil may be, for example, copper or a copper alloy, stainless steel or an alloy thereof, nickel or a nickel alloy (including alloy 42), aluminum or an aluminum alloy. In general flexible metal foil laminates, copper foils such as rolled copper foils and electrolytic copper foils are often used, and are also preferably usable in the present invention. In addition, the surface of these metal foils may be coated with an anti-rust layer, a heat-resistant layer, or an adhesive layer. In the present invention, the thickness of the metal foil is not particularly limited, and may be any thickness that allows the metal foil to exhibit sufficient function depending on the application. The flexible metal foil laminate according to the present invention may have a structure in which a metal foil is laminated on at least one surface of the multilayer polyimide film. EXAMPLES

[0031] The action and effect of the present invention will be described in more detail below through specific manufacturing examples and examples of the present invention, however, these manufacturing examples and examples are presented only as examples of the present invention and do not limit the scope of the invention.

[0032] Manufacturing example: Manufacturing of multi-layer polyimide film A first polyamic acid solution used for producing the core layer was prepared by block copolymerization of biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), paraphenylenediamine (PPD) and m-tolidine (MTD). Biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, paraphenylenediamine, m-tolidine, and oxydianiline (ODA) were polymerized to produce a second polyamic acid solution used in the manufacture of the skin layer. The components and composition ratios of the core layer and skin layer are shown in Table 1 below. [Table 1]

[0033] The first polyamic acid solution and the second polyamic acid solution prepared above are co-extruded by co-extrusion, imidized, and then cured to form a core layer having a thickness of 100 nm. A skin layer was formed on each of the opposite sides of the outer surface to prepare a three-layer polyimide film. Here, however, the core layer was produced by co-extruding a first polyamic acid solution, and the skin layer was produced by co-extruding a second polyamic acid solution. In preparing the polyamic acid, the solvent may be an aprotic solvent, typically an amide-based solvent, such as N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methyl-pyrrolidone, or a combination thereof.

[0034] The dianhydride and diamine components may be added in the form of powder, lump, or solution. It is preferable to add them in the form of powder at the beginning of the reaction to proceed with the reaction, and then add them in the form of a solution to adjust the polymerization viscosity. The resulting polyamic acid solution is mixed with an imidization catalyst and a dehydrating agent and applied to a support. Examples of catalysts that can be used include tertiary amines (eg, isoquinoline, β-picoline, pyridine, etc.), and examples of dehydrating agents include, but are not limited to, acid anhydrides.

[0035] Examples and Comparative Examples While producing a three-layer polyimide film according to the above Production Example, the thicknesses of the core layer and the skin layer were adjusted as shown in Table 2 below to produce multilayer polyimide films of Examples 1 to 3 and Comparative Examples 1 to 8. However, Comparative Examples 1 and 8 correspond to single-layer polyimide films. [Table 2] *The thickness of the skin layer in Table 2 corresponds to the total thickness of the skin layers formed on one outer surface of the core layer and the opposite surface of the outer surface. That is, it corresponds to the total thickness of the two skin layers. The two skin layers were formed to the same thickness. Thus, for example, the thickness of one skin layer of the multilayer (three-layer) polyimide film of Example 2 is 5 μm. The dielectric loss factor (Df) and adhesive strength of the prepared polyimide film were measured and are shown in Table 3 below. The dielectric loss factor (Df) and adhesive strength were measured as follows.

[0036] (1) Measurement of dielectric loss factor (Df) The dielectric loss factor (Df) was measured by drying the sample in an oven at 130°C for 30 minutes, leaving it in an environment at 23°C and 50% relative humidity for 24 hours, and then measuring the dielectric loss factor (Df) using a Keysight network analyzer. The dielectric loss factor was measured at 10 GHz using a QWED SPDR resonator.

[0037] (2) Measurement of adhesive strength The adhesive strength was measured by placing Innoflex (1 mil, Epoxy type, Innox product) on both sides of a polyimide film, placing 1 oz copper foil on both sides, placing protective PI on them, and then heating to 180°C and thermocompressing at a pressure of 30 MPa for 1 hour. The film was cut into 15 mm width pieces and then subjected to a 180° peel test. [Table 3] As a result of the measurements, the multi-layer (three-layer) polyimide films of Examples 1 to 3 exhibited the characteristics of a dielectric loss factor of 0.003 or less and an adhesive strength of 1,000 gf / cm or more.

[0038] In contrast, Comparative Example 1, which corresponds to the core layer of the multilayer polyimide films of Examples 1 to 3 and is a single layer having a thickness of 50 μm, had a very low adhesive strength. In addition, the dielectric loss factor increased and the low dielectric properties decreased in Comparative Examples 2 to 7, in which the core layer and / or skin layer was thicker or thinner than the multilayer polyimide films of Examples 1 to 3. On the other hand, the dielectric loss factor increased and the low dielectric properties decreased in Comparative Example 8, which corresponds to the skin layer of the multilayer polyimide films of Examples 1 to 3, is a single layer with a thickness of 50 μm, and also corresponds to the skin layer of the multilayer polyimide films of Examples 1 to 3. Therefore, the multilayer polyimide films of Examples 1 to 3 produced within the appropriate range of the present application all had excellent low dielectric and adhesive properties, but it was confirmed that when the appropriate range of the present application is exceeded, it is difficult to satisfy all of the low dielectric and adhesive properties of the multilayer polyimide film of the present application. In other words, it was confirmed that the multi-layer polyimide film that has excellent low dielectric and adhesive properties and satisfies all of the various conditions applicable to various fields of application is the multi-layer polyimide film manufactured within the appropriate range of the present application.

[0039] The examples of the multilayer polyimide film and the method for manufacturing the multilayer polyimide film of the present invention are merely preferred examples that enable those skilled in the art to easily carry out the present invention, and the present invention is not limited to the above-mentioned examples, and the scope of the present invention is not limited by these examples. Therefore, the true technical scope of protection of the present invention must be determined by the technical ideas of the appended claims. Furthermore, various substitutions, modifications and changes may be made within the scope of the technical ideas of the present invention. It is obvious to a person skilled in the art that such modifications are possible, and it is obvious that parts that can be easily modified by a person skilled in the art are also included in the scope of the present invention. [Industrial Applicability]

[0040] The present invention provides a polyimide film having excellent low dielectric properties and adhesive properties by adjusting the composition ratio and reaction ratio of dianhydride and diamine components. Another object of the present invention is to provide a flexible copper foil laminate that includes a multi-layer polyimide film having excellent adhesive strength and a relatively low dielectric loss factor, and is effective for high-speed transmission and high-speed communication at high frequencies.

Claims

1. at least one skin layer formed on at least one outer surface of the core layer; The dielectric loss factor is 0.003 or less, and the adhesive strength is 1,000 gf / cm or more. Multi-layer polyimide film.

2. The skin layer is formed on one outer surface of the core layer and on the opposite outer surface of the core layer. The multilayer polyimide film according to claim 1 .

3. The total thickness of the multilayer polyimide film is 10 μm or more and 100 μm or less, the thickness of the core layer is 70% or more and 95% or less of the total thickness of the multilayer polyimide film; the total thickness of the skin layers formed on one outer surface of the core layer and on the opposite surface of the outer surface of the core layer is 5% to 30% of the total thickness of the multilayer polyimide film; The multilayer polyimide film according to claim 2 .

4. The core layer comprises a dianhydride acid component including biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA); A polyamic acid solution containing a diamine component including paraphenylenediamine (PPD) and m-tolidine is subjected to an imidization reaction. The multilayer polyimide film according to claim 1 .

5. The skin layer comprises a dianhydride acid component including biphenyltetracarboxylic dianhydride and pyromellitic dianhydride; A polyamic acid solution containing a diamine component including paraphenylenediamine, m-tolidine, and oxydianiline (ODA) is subjected to an imidization reaction. The multilayer polyimide film according to claim 1 .

6. The content of the biphenyltetracarboxylic dianhydride is 50 mol% or more and 70 mol% or less, and the content of the pyromellitic dianhydride is 30 mol% or more and 50 mol% or less, based on 100 mol% of the total content of the dianhydride acid components; the content of the paraphenylenediamine is 60 mol % or more and 80 mol % or less, and the content of the m-tolidine is 20 mol % or more and 40 mol % or less, based on 100 mol % of the total content of the diamine components; The multilayer polyimide film according to claim 4.

7. The core layer comprises a block copolymer comprising two or more blocks. The multilayer polyimide film according to claim 4.

8. The block copolymer includes a first block including 50 mol % to 60 mol % of the biphenyltetracarboxylic dianhydride based on 100 mol % of the total content of dianhydride acid components in the polyimide film, a second block containing the m-tolidine in an amount of 30 mol % to 40 mol % based on 100 mol % of the total content of the diamine components in the polyimide film; The multilayer polyimide film according to claim 7.

9. The content of the biphenyltetracarboxylic dianhydride is 30 mol% or more and 50 mol% or less, and the content of the pyromellitic dianhydride is 50 mol% or more and 70 mol% or less, based on 100 mol% of the total content of the dianhydride acid components; the content of the paraphenylenediamine is 5 mol % or more and 25 mol % or less, the content of the m-tolidine is 60 mol % or more and 80 mol % or less, and the content of the oxydianiline is 5 mol % or more and 25 mol % or less, based on 100 mol % of the total content of the diamine components; The multilayer polyimide film according to claim 5 .

10. The multilayer polyimide film is produced by any one or more methods selected from the group consisting of coextrusion and coating. The multilayer polyimide film according to any one of claims 1 to 9.

11. A multilayer polyimide film according to any one of claims 1 to 9, comprising an electrically conductive metal foil. Flexible metal foil laminate.

12. Comprising the flexible metal foil laminate of claim 11. Electronic components.

Citation Information

Patent Citations

  • Thermoplastic polyimide film, multilayer polyimide film, and flexible metal-clad laminate

    JP2019210342A

  • Polyimide film, metal-clad laminate and circuit board

    JP2021054062A

  • Metal-clad laminates and circuit boards

    JP2022017273A

  • Highly adhesive, low dielectric polyimide film and method for producing the same

    JP2023501633A

  • Highly adhesive and low-dialectric polyimide film and method for producing same

    US20220403109A1